1997
DOI: 10.2166/wst.1997.0102
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy control of coagulation reaction through streaming current monitoring

Abstract: A fuzzy logic controller (FLC) incorporating the streaming current detector (SDC) was utilized in the automatic control of the coagulation reaction. Kaolinite was used to prepare synthetic raw water, and ferric chloride was used as the coagulant. The control set point was decided at a streaming current (SC) of −0.05 and pH of 8.0 from jar tests, zeta potential and streaming current measurements. A bench-scale water treatment plant with rapid mix, flocculation, and sedimentation units, operated in a continuous-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Liu and Wu [96] conducted jar tests and continuous bench-scale experiments with synthetic raw water and ferric chloride as coagulant. They applied a fuzzy logic feed-backward control system with streaming current (set point −0.05) and pH (set point 8.0) as input, and coagulant dose as well as base dose as output parameters.…”
Section: Fuzzy Logic Modelsmentioning
confidence: 99%
“…Liu and Wu [96] conducted jar tests and continuous bench-scale experiments with synthetic raw water and ferric chloride as coagulant. They applied a fuzzy logic feed-backward control system with streaming current (set point −0.05) and pH (set point 8.0) as input, and coagulant dose as well as base dose as output parameters.…”
Section: Fuzzy Logic Modelsmentioning
confidence: 99%
“…Ainsi, d'importants efforts et différentes approches ont été développés pour construire et mettre en oeuvre des modèles de contrôle automatique de la dose de coagulant (BAZER-BACHI et al, 1986;EVANS et ENOCH, 1998;GAGNON et al, 1997;VALENTIN et al, 1999) et des outils de supervision permettant d'optimiser ce procédé de traitement (KAN et HUANG, 1998;LIU et WU, 1997;STANDEN et al, 1997). En ce qui concerne les outils dits de supervision, dans le cas des travaux de KAN et HUANG (1998), même si on parle de supervision ou de suivi, l'essentiel du développement porte sur la détermination automatique de la dose de coagulant grâce à un suivi optique.…”
Section: Introductionunclassified
“…Correlations between streaming current and electrophoretic mobility measurements have shown that the two parameters are linearly related (Liu & Wu, 1997; Dentel et al, 1989). However, an offset exists between streaming current and electrophoretic mobility measurements in such a manner that an electrophoretic mobility value of zero corresponds to a negative streaming current value.…”
Section: Introductionmentioning
confidence: 99%